DUTA LINGKUNGAN PEKANBARU DALAM KAJIAN DRAMATURGI - Kevin Triady; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Competition for the selection of ambassadors is currently rife in various fields, such as education, tourism, to the environment. These events are one of the most popular competitions for the younger generation. Through this competition, the younger generation has the opportunity to develop their potential, and this competition can be a place to seek popularity. Seeing the deteriorating environmental conditions, especially in Pekanbaru City, Dinas Lingkungan Hidup dan Kebersihan Kota Pekanbaru formed Duta Lingkungan Pekanbaru. Duta Lingkungan Pekanbaru is a representation of a group of young people selected through various selections who are expected to be at the forefront of voicing the environmental care movement and become role models for other young generations in the environmental field. This study aims to determine the front and backstage life of Duta Lingkungan Pekanbaru using Ervin Goffman's dramaturgy theory and to find out how the role of Duta Lingkungan Pekanbaru in campaigning for environmental issues. The author uses qualitative research method and uses purposive sampling technique. The data instruments are observation, interview and documentation. Based on dramaturgy analysis, the results of this study can be concluded that there are no contrasting differences between the front and backstage of Duta Lingkungan Pekanbaru. This means that Duta Lingkungan Pekanbaru is doing their job well, not just seeking popularity through this event. In carrying out its role, Duta Lingkungan Pekanbaru established a personal work program and a joint work program, namely #GenZHeTikYuk. Keyword: Duta Lingkungan Pekanbaru, Dramaturgy